Water Polo Game-Related Statistics in Women S International Championships as a Function of Final Score Differences - Garcia-Hermoso, A (Routledge, 2016)
The aims of this study were: (i) to compare water polo game-related statistics by context (winning and losing teams) and final score differences (using three categories – “close” games, “unbalanced” games, and “very unbalanced” games); and (ii) to identify characteristics that mark the differences in performances for each of these three categories of final score differences. The game-related statistics of the 213 women s matches played in seven international championships were analysed. Differences between contexts (winning or losing teams) and final score differences (close, unbalanced, and very unbalanced games) were determined using the chi-squared statistic, also calculating the effect sizes of the differences. A discriminant analysis was then performed applying the sample-splitting method according to context in each final score. It was found that the game-related statistics differentiate the winning from the losing teams in each final score group, with one variable (penalty goals) differentiating winners from losers in close games, 12 in unbalanced games, and 13 (both offensive and defensive variables) in very unbalanced games. In all three types of game, the game-related statistics were shown to discriminate performance (82% or more), with three variables being discriminatory by context (winning or losing teams): goals, offensive fouls, and goalkeeper-blocked shots. © 2018, Routledge. All rights reserved.